Barium and psoriasis: a mini-review and hypothesis linking environmental exposures to ion channel modulation - Zeldin, Jordan; Jordan, Jalin; Thota, Pranav; Vuong, Richard; Jojo, Christeena; Myles, Ian A. (Frontiers in Medicine, 2025)
Psoriasis is a complex autoimmune skin disorder with rising prevalence and significant comorbidities. Although its etiology remains multifactorial, recent epidemiologic and mechanistic studies—including the NHANES-based analysis by Chen et al.—suggest that environmental exposures, particularly to heavy metals may contribute to its pathogenesis. To further understand this association, we reviewed current literature on the pathogenesis of psoriasis and relevant ion channels, as well as the interactions of both with the heavy metal barium. Both epidemiologic and laboratory data highlight a potential link between environmental heavy metal exposure and autoimmune dysregulation in psoriasis. This review offers a novel hypothesis that mechanistically links environmental exposures to psoriasis through ion channel modulation. Further research is warranted to elucidate the precise mechanisms by which barium can influence K+ channel function and inflammasome activation, potentially offering new approaches for therapeutic interventions in psoriasis and other autoimmune disorders.